Pengaruh Pendaftaran Tanah Sistematis Lengkap terhadap Perekonomian Masyarakat di Kelurahan Tegalsari Mandala II Kota Medan - Satria Mariqom Harahap; Imsar Imsar (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Complete Systematic Land Registration (PTSL) is a land registration activity for the first time covering all land registration objects in all regions of the Republic of Indonesia in a village or sub-district area. Full systematic cadastral registration is believed to produce better results and in a relatively short time compared to sporadic cadastral registration. This study examines the influence of land registration and the role of implementing a complete systematic land registration (PTSL) for the community, as well as the obstacles in implementing PTSL in the regions and how to overcome them. Writing with empirical law method. namely research that examines the problem to be discussed, based on facts that are in PTSL in the area of ​​kel. Tegalsari Mandala II city of Medan, and which is then linked to the provisions of the applicable laws and regulations. The types of approaches used are factual approaches, legal approaches, and analytical and conceptual approaches. The conclusion is that the function of ptsl for the community is to function as a tool for economic productivity, promote financial inclusion and act as a living asset (bankable) to facilitate easier access to money and to overcome government problems in increasing development and facilitating the implementation of spatial planning in the region , as well as guaranteeing legal certainty or rights to land belonging to the community and in its implementation there are constraints such as the budget; Measurement; legal events of death; updates and reviews; competent HR department Keywords: Complete Systematic Soil identification, Effect